A six-channel microstrip diplexer for multi-service wireless communication systems - Fouladi, Farhad (Array, 2021)
In this paper, a six-channel microstrip diplexer is designed and fabricated. It operates at 0.75/0.85/1/1.25/1.6/1.8 GHz for multi-service wireless communication systems. It consists of two stub-loaded resonators, which are integrated by coupled lines. The channels are close together, which makes the proposed diplexer suitable for frequency division duplex (FDD) schemes. The proposed structure has a compact size of 0.025 λg2 where λg is the guided wavelength calculated at 0.75 GHz. The other advantages of the introduced multi-channel diplexer are the low insertion losses of 1.62/1.27/0.43/0.53/1.26 and 1 dB, as well as good return losses of 26/26/25/25/21.7 and 22 dB at 0.75/0.85/1/1.25/1.6/1.8 GHz respectively. A good isolation of less than 22 dB is obtained between the channels. In order to design the presented diplexer a designing technique is used which is based on the proposing of an equivalent approximated LC model and calculating the inductors and capacitors. To confirm the simulation results, the introduced diplexer is fabricated and measured.